Factors that influencing public perception towards Takaful (Islamic insurance) / Nur Diyana Abd Aziz and Nurul Nadia Zainal - Abd Aziz, Nur Diyana; Zainal, Nurul Nadia (2013)
This research was conducted in order to identify the factors that influencing public perception towards Takaful (Islamic insurance). Other than that, this research also tries to find out the most factor that effect on public perception towards Takaful. The Takaful concept evolved from individual common interest from the Industrial era of the early 1900’s. Only eighty million out of the world’s 2.5 billion poor are currently covered by some form of micro insurance. In 23 of the poorest 100 countries in the world, there is currently no identified micro insurance activity. The majority of the population is in the low-income bracket. On top of that, society’s awareness and perception on the importance of insurance is rather low. In this paper, it will be stressed that efforts are still needed to be directed towards educating the public on Islamic insurance, to appreciate the protection aspects that insurance can offer. Conventional insurance involves the elements of uncertainty, gambling and interest, all of which are unacceptable under Islamic law. There are anxiety among Muslims regarding the inconsistency of conventional banking and insurance in compliance with Islamic laws. This allowed the creation of a new industry, takaful, which offering risk protection and savings products to the world’s 1.6 billion Muslims. One of the greatest challenges facing the takaful industry is the misconception that it is for Muslims only. Takaful products have attracted even the non-Muslim communities, despite the obvious religious and cultural differences. Nonetheless, the interest shown by non-Muslims and the support of Muslims is not enough to promote the awareness and the growth of takaful and what it has to offer. It is this lack of awareness that presents one of the greatest challenges to the development and growth of the national and global industry